1997
DOI: 10.1111/1523-1747.ep12334205
|View full text |Cite
|
Sign up to set email alerts
|

Transient Expression of Epidermal Filaggrin in Cultured Cells Causes Collapse of Intermediate Filament Networks with Alteration of Cell Shape and Nuclear Integrity.

Abstract: Filaggrin is an intermediate filament-associated protein (IFAP) that aggregates epidermal keratin filaments in vitro and is thought to perform a similar function during terminal differentiation in vivo. To test this function in living cells, we transiently expressed constructs encoding human filaggrin in both simple epithelial cells (COS-7) and rat keratinocytes. Scanning laser confocal microscopy showed that filaggrin-positive cells had collapsed keratin and vimentin intermediate filament (IF) networks, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
88
0
3

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(95 citation statements)
references
References 48 publications
4
88
0
3
Order By: Relevance
“…These observations are consistent with the known role of FLG in keratin intermediate filament aggregation. 40,80 Although the role for FLG in intermediate filament aggregation in IV has been disputed, 81 FLG mutation testing was unavailable at that time. Moreover, keratin intermediate filament integrity, assessed by susceptibility to urea extraction, remains unchanged in the organotypic, siRNA knock-down cultures that we used in these studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations are consistent with the known role of FLG in keratin intermediate filament aggregation. 40,80 Although the role for FLG in intermediate filament aggregation in IV has been disputed, 81 FLG mutation testing was unavailable at that time. Moreover, keratin intermediate filament integrity, assessed by susceptibility to urea extraction, remains unchanged in the organotypic, siRNA knock-down cultures that we used in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, dominant-negative disruption of the cytoskeleton, as occurs with mutations in either keratin 1 or 10 in epidermolytic ichthyosis (epidermolytic hyperkeratosis), blocks lamellar body (LB) secretion, also resulting in a downstream, paracellular permeability barrier defect. 36 Since FLG peptides normally associate with both the CE [37][38][39] and keratin filaments, 40 FLG deficiency could compromise permeability barrier function by either mechanism, by both mechanisms, or by a mechanism that is unique to IV. Although in the pre-genotype era, barrier function was shown to be moderately abnormal in IV and AD patients, [41][42][43][44][45] this has not been assessed in genotyped, FLG-deficient IV patients, and there is little evidence for the mechanisms of a potential barrier defect.…”
mentioning
confidence: 99%
“…Filaggrin has been shown to be associated with nuclear degradation and keratin intermediate filament aggregation. 28,29 Studies have reported that keratohyalin granules with profilaggrin aggregates localise to the perinuclear region sometimes forming deep invaginations at the areas of association. 28,29 This is thought to facilitate entry of cleaved N-terminal domain of profilaggrin into the nucleus, where it favours nuclear degradation.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 Studies have reported that keratohyalin granules with profilaggrin aggregates localise to the perinuclear region sometimes forming deep invaginations at the areas of association. 28,29 This is thought to facilitate entry of cleaved N-terminal domain of profilaggrin into the nucleus, where it favours nuclear degradation. 28 One potential explanation for the altered processing of filaggrin, partially supported by our data, is that filaggrin interacts with nuclear lamins and therefore the persistence of Lamin A/C increases its association with filaggrin intermediates at the nuclear lamina, preventing its processing to more mature forms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation